ByzRev 06.2024.012: Cyril Pavlikianov, Medieval Greek and Slavic Documents of the Athonite Monastery of Hagiou Pavlou (St. Paul) (1010-1580).: Critical Edition and Commentary of the Texts. Sofia: St. Kliment Ohridski University Press, 2023. - Maksimovič, Kirill (The Byzantine Review, 2024)
Cyril Pavlikianov, Medieval Greek and Slavic Documents of the Athonite Monastery of Hagiou Pavlou (St. Paul) (1010-1580). Critical Edition and Commentary of the Texts. Sofia: St. Kliment Ohridski University Press, 2023. 343 pp. - ISBN: 978-954-07-5705-6